2021
DOI: 10.12928/fokus.v11i1.3194
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi Terhadap Organizational Citizenship Behavior Dengan Komitmen Organisasi Sebagai Variabel Mediasi (Studi Kasus Pada Badan Keuangan Dan Aset Daerah Kabupaten Sleman)

Abstract: The purpose of this study was conducted to determine the effect of the relationship between organizational culture and organizational citizenship behavior (OCB) with organizational commitment as a mediating variable. This research was conducted in the Regional Financial Institutions and Assets of Sleman Regency. The sample in this study were all employees of the Regional Financial Institutions and Assets of Sleman Regency. Data collection by distributing questionnaires using a Likert scale to measure indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
4
0
5
Order By: Relevance
“…Research conducted by Sinha et al (2019) was carried out without mediation from organizational commitment so it was found that it did not have a significant positive relationship, however, after an experiment was carried out through the mediation of organizational commitment. Arundita et al (2021) that an organizational culture that can be managed well by a company will have an influence on the commitment given by employees to the organization so that ultimately it will also influence organizational citizenship behavior to mutually increase. Ariani et al (2017) and Arundita et al (2021) Mahayasa et al (2018) found that the relationship between these two variables and the mediation of organizational commitment did not obtain significant positive results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Sinha et al (2019) was carried out without mediation from organizational commitment so it was found that it did not have a significant positive relationship, however, after an experiment was carried out through the mediation of organizational commitment. Arundita et al (2021) that an organizational culture that can be managed well by a company will have an influence on the commitment given by employees to the organization so that ultimately it will also influence organizational citizenship behavior to mutually increase. Ariani et al (2017) and Arundita et al (2021) Mahayasa et al (2018) found that the relationship between these two variables and the mediation of organizational commitment did not obtain significant positive results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Arundita et al (2021) that an organizational culture that can be managed well by a company will have an influence on the commitment given by employees to the organization so that ultimately it will also influence organizational citizenship behavior to mutually increase. Ariani et al (2017) and Arundita et al (2021) Mahayasa et al (2018) found that the relationship between these two variables and the mediation of organizational commitment did not obtain significant positive results. With the large number of studies conducted previously that obtained more significant positive results than non-significant positive results, the second part of the fourth hypothesis: H4b: Organizational culture positively influences Organizational Citizenship Behavior with the mediation of Organizational Commitment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…faktanya bahwa dengan mendorong budaya organisasi pada pegawai dalam menjalankan tugas, maka karyawan akan merasa memiliki tanggung jawab sehingga meningkatkan perilaku OCB. Hal ini sesuai dengan penelitian yang dilakukan oleh [4], [14] dan [20] yang menyatakan bahwa budaya organisasi berpengaruh terhadap Organizational Citizenship Behavior (OCB).…”
Section: H4unclassified
“…Penerapan budaya organisasi yang baik dalam suatu organisasi akan memicu meningkatnya komitmen pegawai terhadap instansi dan diikuti dengan meningkatnya sikap Organizational Citizenship Behavior. Hal ini sesuai dengan penelitian yang dilakukan oleh [20].…”
Section: H9unclassified
See 1 more Smart Citation